Comparing Folks’ Understanding of the Problem of Evil with Philosophers’ Understanding Based on Experimental Philosophy Approach - Jalal Peykani (پژوهشنامه فلسفه دین, 2023)
Experimental philosophy is a new approach in analytic philosophy emerging in the last decade. Experimental philosophy emphasizes the intuitions of ordinary people and compares them with philosophers' intuitions to understand and analyze philosophical problems. One important philosophical and theological issue that can be addressed with such an approach is the problem of evil. Since in the philosophy of religion, the problem of evil is raised in two logical and evidential forms, the research questionnaires were designed to cover both accounts, although more emphasis was placed on the evidential problem of evil. The statistical population of this research was 100 people from different social groups who did not have special studies in philosophical and theological fields. The findings of this research show that the public's sympathy with the logical account of the problem of evil is more than their sympathy with the evidential one. However, the ratio between the answers and all the questions indicates a significant inconsistency in the folks' understanding of the problem of evil and its relationship with theism.